Gastrointestinal dysautonomia as a manifestation of transverse myelitis: Case report: Disautonomía gastrointestinal como manifestación de mielitis transversa: Reporte de caso - Lugo Peláez , Abel (2023)
Inflammatory transverse myelitis is a rare condition that affects one or more levels of the spinal cord. Its etiology includes multiple sclerosis, infectious causes, or disorders within the spectrum of neuromyelitis optica. It presents acutely with motor, sensory, and/or dysautonomic symptoms, such as those related to the gastrointestinal and urinary systems. Diagnosis is based on symptomatology, evolution, and is confirmed by lumbar puncture, magnetic resonance imaging, and complete blood analysis. We present a clinical case of a patient with transverse myelitis who presented with gastrointestinal symptoms, motor symptoms, and was diagnosed with magnetic resonance imaging.